2005
DOI: 10.1536/ihj.46.265
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Gene Expression Specific to Thoracic Aortic Aneurysms: Microarray Analysis of Surgically Resected Specimens

Abstract: SUMMARYChanges in the expression levels of several genes have been described in aortic aneurysm specimens, however, the spectrum of diverse molecular alterations remains to be elucidated. We attempted to identify key molecules that modulate the pathogenesis of aortic aneurysm, using a complimentary DNA microarray carrying approximately 13,000 human genes.Segments of thoracic aortic aneurysms (TAA) and adjacent normal thoracic aortic tissues without aneurysmal changes (NTA) were obtained from 20 patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 27 publications
(26 reference statements)
3
37
0
1
Order By: Relevance
“…Emerging evidence indicates that the metalloproteinase Adamts-1 plays an important role in the pathophysiology of vascular disorders (7,8,10), but the intracellular mechanisms that control Adamts-1 expression during these processes remain poorly understood. In this work, we show that vascular expression of Adamts-1 is induced by mediators of vascular remodeling, such as VEGF, Ang-II, and the proinflammatory cytokines IL-1␤ and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that the metalloproteinase Adamts-1 plays an important role in the pathophysiology of vascular disorders (7,8,10), but the intracellular mechanisms that control Adamts-1 expression during these processes remain poorly understood. In this work, we show that vascular expression of Adamts-1 is induced by mediators of vascular remodeling, such as VEGF, Ang-II, and the proinflammatory cytokines IL-1␤ and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…The MMP gene expression has earlier been reported to be increased in patients suffering from thoracic aortic aneurysms or dissections. [3][4][5][6] The effects of amyloid fibrils or oligomers on cells have been suggested to be of a generic nature, that is, it has been implied that it is the type of aggregation and not the biochemical nature of the peptide that determines the cellular response. It is therefore of interest that other studies have shown that Ab, the amyloidogenic peptide in Alzheimer's disease, induces the production of MMPs, [39][40][41] which have been suggested to be of relevance for the development of intracerebral hemorrhage in patients with cerebral amyloid angiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Increased production or presence of certain matrix metalloproteinases (MMPs), particularly MMP-1, MMP-2 and MMP-9, has been found in both thoracic aortic aneurysms and dissections. [3][4][5][6] The resulting proteolysis leads to weakening of the aortic wall and appears to be a direct cause of the lesions. Why there is an upregulation of MMPs is unknown.…”
mentioning
confidence: 99%
“…Furthermore, consistently decreased superoxide dismutase activity and increased lipid peroxidation products were reported in thoracic aortic dissections as compared to normal aorta (Liao et al, 2008). Some more causal data for ROS in AA has come from the studies, where the gene expression profiles indicated induction of oxidative stress during experimental AAA formation in rats (Yajima et al, 2002) and differential expression of oxidative stress genes in dilated patient aortas in TAAs (Taketani et al, 2005). Recently, ROS has also been implied in changes in mechanical behavior as H 2 O 2 was involved in remodeling across the vessel wall at the early stages of AAA in an apolipoprotein E deficient mice model (Maiellaro-Rafferty et al, 2011).…”
Section: Introductionmentioning
confidence: 99%